2019
DOI: 10.31938/jsn.v5i2.262
|View full text |Cite
|
Sign up to set email alerts
|

PENGIKATAN AFLATOKSIN B1 DENGAN HASIL EKSTRAKSI UMBI ILES-ILES (Amorpophallus oncophylus) SECARA INVITRO

Abstract: Aflatoksin B1 Binding with Tubers of Iles-Iles (Amorpophallus oncophylus) Extract on InvitroAnimal feed plays an important role in determining livestock productivity and food security for humans. Animal feed produced by the animal feed industry is still corn-soya based, its raw material composition is dominated by soybean and corn meal, which is easily contaminated with aflatoxin. Aflatoxin compounds known to cause disruption to both animals and humans, because it is carcinogenic. Some aflatoxin binding method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Additional curcumin as an anti-oxidation and anti-inflammation agent could protect the ileum against acute damage induced by AFB1 administration [21] The results on some samples in this study showed that a high concentration of AFB1 may cause aflatoxicosis to duck, as acknowledged that the toxic level of aflatoxin BI in white Pekin duck was 48 ppb [22]. Fortunately, lycopene and silymarin showed benefits to cope with aflatoxicosis in ducks [9], and in vitro study of an extract of iles-iles (Amorphophallus oncophylus) tuber also showed the ability to reduce the aflatoxin content [23]. Whereas the additional 0.4% sambiloto (Andrographis paniculata) leaf powder was optimal to increase the economic feed efficiency of Mojosari Duck rearing [24].…”
Section: Aflatoxins Contaminant In Feedstuff Samplesmentioning
confidence: 75%
“…Additional curcumin as an anti-oxidation and anti-inflammation agent could protect the ileum against acute damage induced by AFB1 administration [21] The results on some samples in this study showed that a high concentration of AFB1 may cause aflatoxicosis to duck, as acknowledged that the toxic level of aflatoxin BI in white Pekin duck was 48 ppb [22]. Fortunately, lycopene and silymarin showed benefits to cope with aflatoxicosis in ducks [9], and in vitro study of an extract of iles-iles (Amorphophallus oncophylus) tuber also showed the ability to reduce the aflatoxin content [23]. Whereas the additional 0.4% sambiloto (Andrographis paniculata) leaf powder was optimal to increase the economic feed efficiency of Mojosari Duck rearing [24].…”
Section: Aflatoxins Contaminant In Feedstuff Samplesmentioning
confidence: 75%